Effects of In Utero Exposure to Di-n-Butyl Phthalate on Testicular Development in Rat - Ma, Tan (Int J Environ Res Public Health, 2017)
Humans are inevitably exposed to ubiquitous phthalate esters (PAEs). In utero exposure to di-n-butyl phthalate (DBP) induces abnormal development of the testis and reproductive tract in male offspring, which correspond closely with the human condition of testicular dysgenesis syndrome (TDS)-like syndrome. However, the underlying mechanisms have not been elucidated in detail. In this study, pregnant rats were orally exposed to either corn oil (controls) or DBP at three different doses by gavage during Gestational Days 12.5–21.5. Pathological examinations were performed for toxicity evaluation. Proliferation and apoptosis related proteins (ras related dexamethasone induced 1 (Rasd1), mitogen-activated protein kinase kinases1/2 (MEK1/2), Bcl-2, and Bax) were measured for mechanisms exploration. The results showed that different doses of DBP caused male developmental and reproductive toxicity in rats, including the decrease of anogenital distance (AGD), the histological damage of testis, and apoptosis of seminiferous tubule cells. Our data suggested that DBP played chronic and continuous toxic roles on male reproductive system by disrupting expression of Rasd1 and MEK1/2 as well as Bcl-2/Bax ratio. Further research is warranted.